KONTEKS SOSIOKULTURAL MIGRASI INTERNASIONAL: KASUS DI LEWOTOLOK, FLORES TIMUR - Setiadi Setiadi (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1999)
One of the extern factors that caused the socio-cultural change in a society is migration. How the migration process influenced the alteration process were so much influenced by the area of origin. The impact of international migration to the area of origin were influenced by the new value inter relation brought by migrants such as the physical, socio-economic and socio cultural aspect. The research results with an anthropological approach, supported with survey data in one of the sub districts in East Flores, showed that the strength of traditional value in controlling migrant behaviors existed through formalization with various social control systems. This system could eliminate the negative impact of migration, even though the condition could cause a society dynamic block. The physical condition of the research area that could not be developed also made it more hampered. Hence, modernization and the area development process could not be spurred with international migration.